2018
DOI: 10.18632/oncotarget.24330
|View full text |Cite
|
Sign up to set email alerts
|

Aging-related dysregulation in enteric dopamine and angiotensin system interactions: implications for gastrointestinal dysfunction in the elderly

Abstract: Gastrointestinal dysfunction is a common problem in the elderly. Aging-related changes in interactions between local dopaminergic and renin-angiotensin systems (RAS) have been observed in the brain, renal and vascular tissues. However, it is not known if these interactions also occur in the gut, and are dysregulated with aging. We showed a mutual regulation between the colonic dopaminergic system and RAS using young and aged mice deficient for major angiotensin and dopamine receptors.Aged rats showed a marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…The results showed that genetic deficiency of ATR1 resulted in increased expression of either type 1 and 2 dopamine receptors in the proximal colon. Moreover, an increased ratio of ATR1 to ATR2 was observed in the gut upon genetic deficiency of either DRD1 or DRD2 [79]. Thus, this study confirms a reciprocal negative regulation between the pro-inflammatory receptor ATR1 and the anti-inflammatory receptors ATR2, DRD1, and DRD2.…”
Section: Modulation Of Inflammation By Dopamine and Rassupporting
confidence: 81%
See 1 more Smart Citation
“…The results showed that genetic deficiency of ATR1 resulted in increased expression of either type 1 and 2 dopamine receptors in the proximal colon. Moreover, an increased ratio of ATR1 to ATR2 was observed in the gut upon genetic deficiency of either DRD1 or DRD2 [79]. Thus, this study confirms a reciprocal negative regulation between the pro-inflammatory receptor ATR1 and the anti-inflammatory receptors ATR2, DRD1, and DRD2.…”
Section: Modulation Of Inflammation By Dopamine and Rassupporting
confidence: 81%
“…Thus, this study confirms a reciprocal negative regulation between the pro-inflammatory receptor ATR1 and the anti-inflammatory receptors ATR2, DRD1, and DRD2. Interestingly, the same authors also demonstrated that aged rats, which are associated with a pro-inflammatory state on the gastrointestinal tract, display higher levels of ATR1 expression and lower expression of ATR2 and DRD2 in the colon, differences that could be partially reverted by the administration of the ATR1 antagonist candesartan [ 79 ]. Taken together, these results indicate that gut homeostasis involves a reciprocal regulation between some components of the RAS and the dopaminergic system, which becomes dysregulated upon inflammation associated to IBD and ageing, resulting in increased pro-inflammatory signaling mediated by ATR1 and DRD3, and impaired anti-inflammatory signaling mediated by ATR2, DRD1, and DRD2.…”
Section: Modulation Of Inflammation By Dopamine and Rasmentioning
confidence: 99%
“…The interaction also occurs in the periphery. Aged rats showed a marked decrease in colonic dopamine D 2 receptor expression together with an increase in AT1 receptor expression, and candesartan induced a significant increase in the expression of dopamine D 2 receptors . Besides, counter regulatory interactions between dopamine and Ang II were observed in kidney degeneration, hypertension, and the nigrostriatal system …”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the physiological aging process affects the local expression of RAS. Garrido-Gil et al ( 128 ) reported that older rats showed higher colonic expression of the AT1 receptor but lower expression of the AT2 receptor than younger rats. Also, the ACE1/ACE2 ratio was elevated in adult rats compared with juvenile animals in the jejunum and colon.…”
Section: Ras and Gut Microbiota In Health And Diseasementioning
confidence: 99%